Discover the best answers to your questions with the help of IDNLearn.com. Our experts are available to provide in-depth and trustworthy answers to any questions you may have.
Sagot :
To solve for the value of the polynomial function [tex]\( g(x) \)[/tex] at [tex]\( x = -1 \)[/tex], we will follow these steps:
Given the polynomial [tex]\( g(x) = x^3 + 6x^2 + 12x + 8 \)[/tex],
1. Substitute [tex]\( x = -1 \)[/tex] into the polynomial equation:
[tex]\[ g(-1) = (-1)^3 + 6(-1)^2 + 12(-1) + 8 \][/tex]
2. Compute each term individually:
- Compute [tex]\( (-1)^3 \)[/tex]:
[tex]\[ (-1)^3 = -1 \][/tex]
- Compute [tex]\( 6(-1)^2 \)[/tex]:
[tex]\[ (-1)^2 = 1 \quad \text{so} \quad 6 \cdot 1 = 6 \][/tex]
- Compute [tex]\( 12(-1) \)[/tex]:
[tex]\[ 12 \cdot (-1) = -12 \][/tex]
- The constant term is [tex]\( 8 \)[/tex].
3. Add these computed values together:
[tex]\[ g(-1) = -1 + 6 - 12 + 8 \][/tex]
4. Simplify the expression step by step:
- First combine [tex]\(-1\)[/tex] and [tex]\(6\)[/tex]:
[tex]\[ -1 + 6 = 5 \][/tex]
- Then combine [tex]\(5\)[/tex] and [tex]\(-12\)[/tex]:
[tex]\[ 5 - 12 = -7 \][/tex]
- Finally, combine [tex]\(-7\)[/tex] and [tex]\(8\)[/tex]:
[tex]\[ -7 + 8 = 1 \][/tex]
Therefore, [tex]\( g(-1) = 1 \)[/tex].
So the value of the function when [tex]\( x = -1 \)[/tex] is [tex]\( g(-1) = 1 \)[/tex].
Given the polynomial [tex]\( g(x) = x^3 + 6x^2 + 12x + 8 \)[/tex],
1. Substitute [tex]\( x = -1 \)[/tex] into the polynomial equation:
[tex]\[ g(-1) = (-1)^3 + 6(-1)^2 + 12(-1) + 8 \][/tex]
2. Compute each term individually:
- Compute [tex]\( (-1)^3 \)[/tex]:
[tex]\[ (-1)^3 = -1 \][/tex]
- Compute [tex]\( 6(-1)^2 \)[/tex]:
[tex]\[ (-1)^2 = 1 \quad \text{so} \quad 6 \cdot 1 = 6 \][/tex]
- Compute [tex]\( 12(-1) \)[/tex]:
[tex]\[ 12 \cdot (-1) = -12 \][/tex]
- The constant term is [tex]\( 8 \)[/tex].
3. Add these computed values together:
[tex]\[ g(-1) = -1 + 6 - 12 + 8 \][/tex]
4. Simplify the expression step by step:
- First combine [tex]\(-1\)[/tex] and [tex]\(6\)[/tex]:
[tex]\[ -1 + 6 = 5 \][/tex]
- Then combine [tex]\(5\)[/tex] and [tex]\(-12\)[/tex]:
[tex]\[ 5 - 12 = -7 \][/tex]
- Finally, combine [tex]\(-7\)[/tex] and [tex]\(8\)[/tex]:
[tex]\[ -7 + 8 = 1 \][/tex]
Therefore, [tex]\( g(-1) = 1 \)[/tex].
So the value of the function when [tex]\( x = -1 \)[/tex] is [tex]\( g(-1) = 1 \)[/tex].
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Find clear and concise answers at IDNLearn.com. Thanks for stopping by, and come back for more dependable solutions.